Experiences as a Strategy for Strengthen Critical Thinking in Rural Education - Torres Cruz, Doris Lilia; Fonseca Villamil, Widy Patricia; Pineda Jaimes, Blanca Nieves (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents the results obtained when implementing a pedagogical strategy aimed at strengthening critical thinking through oral argumentation, based on the student ‘s experiences and context, which generated spaces of interaction that allowed him to understand and take a stand against the problematic Social and environmental aspects of their environment and life experiences. In order to do so, we used Henry Giroux (1990) and Paulo Freire (2005), who propose “a reflexive and critical thinking that questions, analyzes and interprets the reality in which we live.” The relevant aspects in the design of the strategy, structured in four stages, are: thematization, experiential appropriation, problematization and argumentation based on the use of argumentative sequences, which provide the opportunity to verbally express knowledge, concerns, knowledge, reasoned arguments and propose solutions to problems in the rural context. It is concluded that when facing the child with his reality from praxis, interests and experiences, they develop thinking skills that strengthen the construction of meaningful knowledge, which make him an active agent, participatory and with critical awareness of the teaching-learning process.